Uncovering key molecules and immune landscape in cholestatic liver injury: implications for pathogenesis and drug therapy - Song, Shuailing; Li, Xiao; Geng, Chong; Guo, Yaoyu; Yang, Yi; Wang, Chunhui (Frontiers in Pharmacology, 2023)
Background: Cholestasis is a common pathological process in a variety of liver diseases that may lead to liver fibrosis, cirrhosis, and even liver failure. Cholestasis relief has been regarded as a principal target in the management of multiple chronic cholestasis liver diseases like primary sclerosing cholangitis (PSC) and primary biliary cholangitis (PBC) at present. However, complicated pathogenesis and limited acknowledgments fettered therapeutic development. Therefore, this study aimed to systematically analyze miRNA-mRNA regulatory networks in cholestatic liver injury in order to provide new treatment strategies. Methods: Gene Expression Omnibus (GEO) database (GSE159676) was used to screen differentially expressed hepatic miRNAs and mRNAs in the PSC vs. control comparison and the PBC vs. control comparison, respectively. MiRWalk 2.0 tool was used to predict miRNA-mRNA pairs. Subsequently, functional analysis and immune cell infiltration analysis were performed to explore the pivotal functions of the target genes. RT-PCR was used to verify the result. Results: In total, a miRNA-mRNA network including 6 miRNAs (miR-122, miR-30e, let-7c, miR-107, miR-503, and miR-192) and 8 hub genes (PTPRC, TYROBP, LCP2, RAC2, SYK, TLR2, CD53, and LAPTM5) was constructed in cholestasis. Functional analysis revealed that these genes were mainly involved in the regulation of the immune system. Further analysis revealed that resting memory CD4 T cells and monocytes could potentially participate in cholestatic liver injury. The expressions of DEMis and eight hub genes were verified in ANIT-induced and BDL-induced cholestatic mouse models. Furthermore, SYK was found to have an impact on the response to UDCA, and its mechanism was possibly associated with complement activation and monocyte reduction. Conclusion: In the present study, a miRNA-mRNA regulatory network was constructed in cholestatic liver injury, which mostly mediated immune-related pathways. Moreover, the targeted gene SYK and monocytes were found to be related to UDCA response in PBC.